Itc at the benefit of integrated urban conservation. recife, pernambuco, brasil (2010)
The article analyzes the area intended to support seaport activities in the city of Recife, in the XVII to XIX centuries, and now hosts the Digital Port of Pernambuco. The aim is to demonstrate how Information Technology and Communication, ICT, can contribute to integrated urban conservation through the dissemination of historical and cultural values attributed to the urban complex, both tangible and intangible. The use of historical method feeds the application of the theory of urban morphology and complements the conceptual scaffolding of interpretive planning and integrated conservation.